Efficacy and Effects of Parenteral Pethidine or Meptazinol and Regional Analgesia for Pain Relief during Delivery. A Comparative Observational Study - Singer, J.; Jank, A.; Amara, S.; Stepan, P. D. H.; Kaisers, U.; Hoehne, C. (Geburtshilfe und Frauenheilkunde, 2016)
Background: Peripartum anesthesia may consist of parenteral opioids and/or regional analgesia. There is only limited data in the literature comparing both methods in daily obstetric practice. This observational study investigated the opioids pethidine and meptazinol as well as regional analgesics with regard to their administration, efficacy, side effects and subjective maternal satisfaction with therapy. The rates of secondary regional analgesia administration after administration of the respective opioid served as a means of evaluating treatment.Methods: This study collected data on pain management during vaginal delivery in a German university hospital over a twelve month period. Severity of pain was measured intrapartum using a numerical rating scale. Maternal, neonatal and delivery-related data were obtained postpartum from the clinical records and from the mothers using a questionnaire.Results: The study is based on data obtained from 449 deliveries. Pain relief achieved by the administration of pethidine and meptazinol was similarly low; maternal satisfaction with the respective therapy was high. Meptazinol was usually administered intravenously (83 % vs. 6 %; p < 0.001), repeatedly (27 % vs. 6 %; p < 0.001) and closer to the birth (1.9 ± 2.7 h vs. 2.6 ± 2.8 h; p < 0.05) compared to pethidine. Secondary regional analgesia was more common after the administration of pethidine (16 % vs. 8 %; p < 0.05). Regional analgesia resulted in greater pain relief compared to opioid therapy (78 % vs. 24 % after 30 min; p < 0.001) and was associated with longer times to delivery (7.6 ± 2.5 h vs. 5.7 ± 2.5 h; p < 0.001) and higher levels of maternal satisfaction with therapy (6.1 ± 1.2 vs. 4.8 ± 1.6 on a 7-point scale; p < 0.001).Conclusion: In daily clinical practice, meptazinol can be adapted more readily to changes during birth and requires less secondary analgesia. Regional neuraxial analgesia was found to be an efficacious and safe way of managing labor pain.
Keywords: regional anesthesia; obstetrics; pain therapy